ChemInform Abstract: The Catalytic Application of Recoverable Magnetic Nanoparticles‐Supported Organic Compounds. Issue 38 (30th August 2013) - Xu, Hua‐Jian; Wan, Xin; Geng, Ye; Xu, Xiao‐Lan
Abstract Review: 185 refs.